Pendekatan Diagnosis dan Tata Laksana Alopesia Androgenetik - Ardhiah Iswanda Putri; M Yulianto Listiawan (MEDICINUS, 2022)
Androgenetic alopecia (AGA) is the most common form of alopecia, and affects both men and women. It is described as a progressive reduction in hair diameter, length, and pigmentation. The early signs of AGA can begin in adolescence, where family history is the most predisposing factor. AGA interferes with physical appearance which is an important factor in human self-image. Patients suffering from AGA can experience a significant reduction in quality of life, so they tend to seek for effective hair loss treatments to prevent further thinning and stimulate optimal regrowth. Unfortunately, drugs that have been approved for the treatment of AGA are still limited, have some potential side effects, and do not always give satisfactory results. The limited efficacy of the therapeutic regimen, poor tolerance, and lack of information about the duration of treatment as well as possible side effects can affect adherence to medications, also lead to disappointment and early discontinuation of treatment. Therefore, comprehensive AGA management and proper education are essential to obtain optimal results in the management of AGA.